Nieznane wspomnienie o biskupie Adamie Prosperze Burzyńskim - Ziółek, Ewa M. (Archiwa, Biblioteki i Muzea Kościelne, 2016)
The published source is Rev. Jan Chryzostom Dąbrowski’s memoirs about the Bishop of Sandomierz Adam Prosper Burzyński (1755-1830). It is a hitherto unknown and newly discovered manuscript in the collection of the Library of the Catholic University of Lublin (KUL). It presents an interesting person, a missionary in Egypt in his youth and from 1820 onwards the bishop and organizer of the Diocese of Sandomierz. It includes both Burzynski’s memoirs about missions in the Middle East, which were told to his seminarians by him, as well as a description of the life of the seminarians in the 1820s. The author, Rev. Dabrowski, was also an interesting person. His clerical career was interrupted by the January Uprising, as he was exiled to stay in Siberia for supporting it; and after his return to the country in 1870, the tsarist authorities did not allow him to perform any function in the diocese.